Identification of Key Parameters for Cover Audio Generation in Imperceptible Audio Steganography - Muhammad Harith Noor Azam; Farida Hazwani Mohd Ridzuan; A H Azni; Sakinah Ali Pitchay; Nur Hafiza Zakaria (Usim Press, 2026)
Indexed by MyCite